2001
DOI: 10.1038/sj.bmt.1703272
|View full text |Cite
|
Sign up to set email alerts
|

Association between high interleukin-6 levels and adverse outcome after autologous haemopoietic stem cell transplantation

Abstract: Summary:We studied interleukin-6 (IL-6) levels on the day of transplantation in 31 patients undergoing autologous haemopoietic stem cell transplantation (SCT) (either peripheral blood stem cell transplantation (PBSCT) or bone marrow transplantation (BMT)) for neoplastic diseases to determine if there was a relationship between IL-6 level and rate of haemopoietic recovery, length of stay in hospital, and survival. There was no apparent delay in post-transplant recovery associated with elevated IL-6 levels. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
10
0
3
Order By: Relevance
“…HCT studies have focused on inflammatory biomarkers post-conditioning and/or serially evaluated to predict outcome 34,35. Higher levels post-HCT have been associated with increased transplantation related complications in some studies 34,36,37 and with worse survival in others 24,38. Schots and colleagues analyzed IL-6, interleukin-8 and tumor necrosis factor-alpha levels serially in 84 patients after HCT.…”
Section: Discussionmentioning
confidence: 99%
“…HCT studies have focused on inflammatory biomarkers post-conditioning and/or serially evaluated to predict outcome 34,35. Higher levels post-HCT have been associated with increased transplantation related complications in some studies 34,36,37 and with worse survival in others 24,38. Schots and colleagues analyzed IL-6, interleukin-8 and tumor necrosis factor-alpha levels serially in 84 patients after HCT.…”
Section: Discussionmentioning
confidence: 99%
“…28 This possible rescue of chemotherapy-treated tumour cells by IL-6 may explain why serum IL-6 levels postautologous transplantation were shown to be predictors of poor response after high-dose chemotherapy and autologous transplantation in various cancers. 46 We also have to emphasize that the anti-IL-6 mAb might have potentiated the apoptotic effect of DEX given just before HDM since numerous studies have shown that IL-6 can block the DEX-induced apoptosis of myeloma cells in vitro. This was the reason why we decided to inject DEX just before HDM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among non-orthopedic surgery studies, IL-6 on the day of haemopoietic stem cell transplantation predicted hospital length of stay (Tegg et al, 2001). Peri-operative lidocaine has been found to affect hospital length of stay for some abdominal surgeries.…”
Section: Early Post Surgical Status and Hospital Length Of Staymentioning
confidence: 99%